Balancing cardiovascular benefit and diabetogenic harm of therapy with statins: Real-world evidence from Italy. (June 2020) - Corrao, Giovanni; Monzio Compagnoni, Matteo; Cantarutti, Anna; Rea, Federico; Merlino, Luca; Catapano, Alberico L.; Mancia, Giuseppe
Abstract: Aim: To provide information on the balance between the cardiovascular (CV) benefit and the diabetogenic harm of statin therapy in the current clinical practice. Methods: All the 115, 939 residents (older than 50 years) in the Italian Lombardy Region newly treated with statins between 2003 and 2005, were followed from the first statin prescription until 2012 to identify those experiencing a macrovascular complication and those with at least one sign suggestive of new onset diabetes. The proportion of days of follow-up covered by statin prescriptions measured adherence with statins. Hazard ratio, and relative 95% confidence interval (CI), for the two considered outcomes associated with statin adherence, were separately estimated (proportional hazard models). Number needed to treat (NNT) and number needed to harm (NNH), i.e., number of individuals who must be treated with statins in order to prevent a macrovascular complication, or to generate a new onset diabetes, respectively, were calculated to evaluate the balance between CV benefit and diabetogenic harm of statin therapy. Results: Compared to those at very low adherence with statins, patients at high adherence showed a significant reduction of macrovascular risk (28%, 95% CI: 23%–33%) and a greater risk of developing diabetic condition (67%, 50%-86%). In the whole cohort, the NNT was 26, whereas the NNH 65. NNT was lower than NNH also in all considered strata of age, gender, clinical profile. Conclusions: This large cohort investigation provides real-world evidence that the balance between CV benefit and diabetogenic harm of statin therapy is largely favourable to treatment benefits.